Laparoscopic Treatment of Median Arcuate Ligament Syndrome: A Case Report - Girgin, Mustafa; Cetinkaya, Ziya; Artas, Hakan; Kanat, Burhan Hakan (Gazi Univ, Fac Med, 2012)
In patients with persistent abdominal pain for which another cause has not been found in the etiology, even if rarely, it should be suspected that, even though rare, the compressing effect of the median arcuate ligament of the diaphragm on the celiac truncus may be the cause of this ischemic pain. It is known as the Median Arcuate Ligament Syndrome. If preliminary investigation has been made, this condition is quite simple in both diagnosis and treatment. This syndrome may negatively affect the lives of many patients if not diagnosed and treated in time. In this case report we are presenting a patient with an isolated median arcuate syndrome who was treated by laparoscopy.
Median Arkuat ligaman sendromunun laparoskopik tedavisi: Olgu sunumu
Keywords: Median arcuate syndrome; persistent abdominal pain; laparoscopic treatment